2021
DOI: 10.1111/myc.13354
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the RealStar®Pneumocystis jirovecii PCR kit for the diagnosis of Pneumocystis pneumonia

Abstract: Background Pneumonia due to Pneumocystis jirovecii (PCP) is a frequent infection in HIV‐positive and also in immunocompromised HIV‐negative patients. PCR analysis of pulmonary samples has become an essential element in PCP laboratory diagnosis. Currently, many commercially PCR‐based tests are available for P jirovecii detection and need to be evaluated. Objectives We evaluated the performance of the RealStar® P jirovecii PCR kit for PCP diagnosis. Methods We performed the RealStar® P jirovecii PCR and an in‐ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recent studies have demonstrated the superior sensitivity of the DiaSorin PJP assay when compared to a direct immunofluorescence assay ( 28 ) and its clinical usefulness for the diagnosis and management of PJP in correlation with clinical data and pathology testing ( 27 ). The RealStar assay has shown excellent concordance with several other molecular PJP assays and has been reported to detect low burdens of P. jirovecii in respiratory specimens ( 24 26 ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Recent studies have demonstrated the superior sensitivity of the DiaSorin PJP assay when compared to a direct immunofluorescence assay ( 28 ) and its clinical usefulness for the diagnosis and management of PJP in correlation with clinical data and pathology testing ( 27 ). The RealStar assay has shown excellent concordance with several other molecular PJP assays and has been reported to detect low burdens of P. jirovecii in respiratory specimens ( 24 26 ).…”
Section: Introductionmentioning
confidence: 87%
“…Both in-house and commercial real-time PCR assays for the detection of P. jirovecii using different gene targets have been developed ( 20 , 22 , 23 ). Among P. jirovecii real-time PCR assays on the market today are the altona RealStar Pneumocystis jirovecii PCR kit 1.0 ( 24 26 ) and the DiaSorin P. jirovecii real-time assay ( 27 , 28 ). Both assays target the multicopy mitochondrial large-subunit rRNA ( mtLSU ) gene ( 26 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, molecular detection methods have gradually been developed to detect Pj . Polymerase chain reaction (PCR) assays, which mainly target the mitochondrial large subunit rRNA gene and the multicopy major surface glycoprotein gene family, make the detection of Pj more sensitive than microscopic detection [ 7 , 8 ]. However, no commercial PCR kits have been approved for clinical use in China, and their sensitivity is unsatisfactory [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the samples obtained by bronchoscopy provide a better score of positive detection. However, collecting this type of sample requires invasive medical management, therefore this procedure is not usually performed in many countries to identify the pathogen [1,7]. In view of this limitation, formalin-fixed and paraffin-embedded tissues (FFPE) could be alternative sources of samples for molecular studies [8,9].…”
Section: Introductionmentioning
confidence: 99%